ÜLKEMİZDE SAĞLIK KURUMLARINDA İŞ SAĞLIĞI VE GÜVENLİĞİ - GELDİ, MEHMET (Fırat Üniveristesi, 2017)
Sağlık kurumlarında iş kazaları ve meslek hastalıklarının önlenmesinde İş Sağlığı ve Güvenliği önlemlerinin büyük etkisi bulunmaktadır. Bu nedenle sağlık personelinin sağlıklı ve güvenli ortamlarda çalışmasına engel olan faktörler, sağlık kurumları yönetimlerinin en önemli sorunlarından birisi olmaya devam etmektedir. Sağlık sektöründe meydana gelen iş kazası ve meslek hastalığı, diğer sektörlere oranla daha ölümcül olabilmektedir. Bu nedenle sağlık kurumlarında iş sağlığı ve güvenliğini korumak amacıyla ilk kez özel bir kanunla 6331 sayılı İş Sağlığı ve Güvenliği Yasası çıkarılmış ve bu Yasa ile birlikte Devlet, işçi ve işverenin yükümlülükleri arttırılmış, işçi ve memur ayrımı kaldırılarak tüm çalışanlar kapsam içine alınmıştır. Bu sayede iş kazası geçirme ve meslek hastalığına yakalanma sayıları düşürülmeye çalışılmıştır. Çalışmamızda iş sağlığı ve güvenliğinin önemini kavramak için İSG hakkında genel bilgilere değinilmiş, faaliyet gösteren kuruluşlar ele alınmış ve yasal düzenlemeler hakkında detaylı bilgilere yer verilmiştir. Ayrıca bu yasanın kamu ve özel sağlık kurumlarında uygulanması ile birlikte devlet, işçi ve işverenin sorumluluklarına değinilerek teorik bir çalışma sağlanmıştır. Çalışma sonucunda sağlık kurumlarında meydana gelen iş kazası ve meslek hastalıklarının önlenmesi, maddi ve manevi kayıpların yaşanmaması ve personelin daha güvenli koşullarda çalışması için işletmelerin İSG kurallarına mutlak uyması gerektiği görülmüştür. Anahtar Kelimeler: Sağlık, Güvenlik, İş Sağlığı, İş Güvenliği, İş Kazası, Meslek Hastalığı.

Occupational Health and Safety measures have a great impact on Occupational accidents and prevention of professional diseases in health institutions. For this reason, factors that prevent working health personnel in a healthy and safe environment continue to be one of the most important problems of the healthcare administration. Occupational accidents and professional diseases that occur in the health sector can be more fatal than other sectors. For this reason, Law No. 6331 on Occupational Health and Safety was issued for the first time by a special law in order to protect occupational health and safety in health institutions. For this reason, the Law No. 6331 on Occupational Health and Safety was enacted for the first time in order to protect health and safety in health institutions with a special law. With this law, the obligations of the state, workers and employers have been increased and workers and civil servants have been removed. In this respect, it is tried to reduce the number of occupational accidents and professional diseases. In order to understand the importance of occupational health and safety in our study, general information about the OHS is addressed, the organizations operating are handled and detailed information on legal regulations is given. In addition, a theoretical work has been prepared by referring to the responsibilities of state, workers and employers with the application of this law in public and private health institutions. As a result of the study, it has been seen necessary to comply with OHS rules absolutely, in order to prevent occupational accidents and occupational diseases, lack of material and moral losses, and to ensure that employees work in safer conditions. As a result of the study, in order to prevent occupational accidents and occupational diseases, lack of material and moral losses, and to ensure that employees work in safer conditions. Key words: Health, Security, Occupational Health, Occupational Safety, Work Accident, Occupational Disease.
Occupational health and safety in Turkey health care institutions
Keywords: İşletme; Sağlık Kurumları Yönetimi; Çalışma Ekonomisi ve Endüstri İlişkileri